An exploration of students’ creativity through a mixed-methods study in the classroom - Aziz, Rahmat; Maimun, Agus; Hamid, Abdul; Masturin, Masturin; Efiyanti, Alfiana Yuli (Journal of Education and Learning (EduLearn), 2025)
Students’ creativity is a fundamental goal in education. The school has a strategic role in developing students’ creativity. This study elaborates on classroom activities to develop students’ creativity. The study used a mixed-method sequential explanatory design. Quantitative data were obtained from six hundred and one students from junior and senior high schools in East Java, Indonesia. Qualitative data were obtained from nine teachers. Descriptive and regression analysis techniques are used to analyse quantitative data, while thematic analysis is used to analyse qualitative data. The results show that the hypothesis is accepted. It means that classroom climate affects students’ creativity. The findings also showed three classroom activities for developing students’ creativity: rule, positive teaching and teacher support. Teachers’ ability to manage learning in the classroom affects the high level of students’ creativity.